Effect of self-esteem and credit card misuse on online shopping addiction - Aslan, Melda (Journal of Dependence, 2023)
Objective: The aim of this study, is to determine the effect of self esteem and credit card misuse on online shopping addiction in young adults. Method: 388 young adults voluntarily participated in the study. In this study, which based on the relational screening model, the Self-esteem Scale, the Credit Card Misuse Scale, and the Online Shopping Addiction Scale were used. Results: The mean age of the participants was 19.7 years, and 213 (%54,9) were female. Self-esteem was found to predict online shopping addiction by %56.4 in young adults. However, self-esteem and credit card misuse was found to predict online shopping addiction by %80.2 in young adults. According to time spent on the internet, there were significant differences in self-esteem, credit card misuse, and online shopping addiction. Conclusion: According to research findings, it can be asserted that young adults’ expectations to obtain social status and social conformity through the acquisition of a product may affect spending time for online shopping and they may lose control of the use of credit cards..